Resposta :
Resposta:
OLÁ
[tex]f(x) = 3x + 20 \\ substitui \: o \:( x )\: por \: - 2.5 \\ f(x) = 3x + 20 \\ f( - 2.5) = 3 \times ( - 2.5) + 20 \\ f( - 2.5) = - 7.5 + 20 \\ f( - 2.5) = 12.5 \\ letra \: (c) \: espero \: ter \: ajudado[/tex]
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/dd5/55bde67b23f015a3736926843a006b7c.jpg)
Resposta:
OLÁ
[tex]f(x) = 3x + 20 \\ substitui \: o \:( x )\: por \: - 2.5 \\ f(x) = 3x + 20 \\ f( - 2.5) = 3 \times ( - 2.5) + 20 \\ f( - 2.5) = - 7.5 + 20 \\ f( - 2.5) = 12.5 \\ letra \: (c) \: espero \: ter \: ajudado[/tex]